2010
DOI: 10.1590/s0074-02762010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Mansonella ozzardi in Amazonas, Brazil: prevalence and distribution in the municipality of Coari, in the middle Solimões River

Abstract: 51 years old (26.9% urban and 61.5% rural). High prevalence rates were observed in retired people (27.1% urban area), housewives and farmer (41.6% and 25%, respectively, in rural area). The main clinical symptoms were joint pains and sensation of leg coldness. Only Cerqueirellum argentiscutum (Simuliidae) transmits M. ozzardi in this municipality (PIR = 5.6% urban and 7.1% rural). M. ozzardi is a widely distributed parasitic disease in Coari. Thus, temporary residency in the region of people from other localit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
1
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 21 publications
5
46
1
14
Order By: Relevance
“…This study revealed a wide distribution of this filarial parasite in the middle Solimões region and in the high tributaries of the Solimões basin. The M. ozzardi prevalence rates were lower (6.3%) than those previously recorded in Solimões River communities, including rates of 23.9% in Codajás, 10.0 to 17.8% in Coari, 2.5 to 18.7% in Tefé, and 18.4 to 18.9% in Coari 1,3,4 . In addition, the communities located beside the middle and upper segments of the river presented a higher frequency of M. ozzardi infections, which was possibly related to the greater abundance of black fly vectors.…”
contrasting
confidence: 67%
See 1 more Smart Citation
“…This study revealed a wide distribution of this filarial parasite in the middle Solimões region and in the high tributaries of the Solimões basin. The M. ozzardi prevalence rates were lower (6.3%) than those previously recorded in Solimões River communities, including rates of 23.9% in Codajás, 10.0 to 17.8% in Coari, 2.5 to 18.7% in Tefé, and 18.4 to 18.9% in Coari 1,3,4 . In addition, the communities located beside the middle and upper segments of the river presented a higher frequency of M. ozzardi infections, which was possibly related to the greater abundance of black fly vectors.…”
contrasting
confidence: 67%
“…In addition, our results are in agreement with those of Batista et al 5 , Shelley 6 , and Medeiros et al 7 , who found no statistically significant difference in the prevalence rates between sexes. However, other epidemiological studies have reported a higher disparity between the prevalence rates in males and females 4,8 .…”
mentioning
confidence: 76%
“…Later, some researchers observed individuals infected with M. ozzardi alongside the Solimoes, Purus and Negro Rivers in the State of Amazonas [4][5][6] . Recent data have indicated that this parasite is still found with high prevalence rates in the Amazonian territory [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Mansonella ozzardi is a widely distributed fi laria worm that parasitizes humans in Amazonas State, Brazil, with high prevalences detected in residents of some regions of the Solimões, Negro, and Purus Rivers (1) (2) (3) (4) (5) . Simuliidae (blackfl ies) are the only vector of M. ozzardi in Brazil (6) (7) .…”
mentioning
confidence: 99%
“…This is possibly one of the factors responsible for accumulation of parasites in individuals, maintaining several adult worms of different ages with continuous production of microfi lariae, infection, and transmission by insect vectors (3) (5) . There are no previous reports of residence duration and prevalence rates of mansonelliasis; however, this relationship possibly also occurs in other regions.…”
mentioning
confidence: 99%